วาทกรรมการเมืองไทยผ่านภาษาในบทบรรณาธิการหนังสือพิมพ์ ระหว่างการชุมนุม 193 วัน ของกลุ่มพันธมิตรประชาชนเพื่อประชาธิปไตย - อภิวิชญ์ ไพศาลทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This research aims at studying Thai Political Discourse in newspaper editorials during the peopleKs Alliance for Democracy (PAD) 193 O Day assembly which has the study scope during is May 2008 O 13 December 2008. The study can be divided into 3 periods. Firstly, before assembly period since 15 May 2008 O 25 May 2008. Secondly, the assembly start until end period since 25 May 2008 O 3 December 2008. Lastly, after assembly period since 3 December 2008 O 13 December 2008. Using Qualitative Research method by historical approach and focus on content analysis by using Discourse Theory. The research found that Discourse during 193 O Day assembly of the peopleKs Alliance for Democracy (PAD) in newspaper editorials have 15 Sub- Discourse from 7 newspaper studied. The purpose was to present the same persuasive point in order to make the reader follows and agrees with newspaper. The main discourse can be divided into 3 types (Build trust for The peopleKs Alliance for Democracy (PAD), Build trust for Government and offer the solution of argument) The overall Presentation of newspaper seems to discredit the Government working performance more than discredit the assembly of the peopleKs Alliance for Democracy (PAD) ad refers to the third person to support the presentation